Prevalence of phubbing behaviour in school and university students in Spain - Barbed-Castrejón, Noelia; Navaridas-Nalda, Fermín; Mason, Oliver; Ortuño-Sierra, Javier (Frontiers in Psychology, 2024)
Objective This study examined the prevalence of phubbing behavior among school and university students in Spain and analyzed the correlation of phubbing with other indicators of psychological well-being and mental health. Methods The study sample comprised a total of 1,351 school and university students, with ages ranging from 12 to 21 years. The study used the Phubbing Scale (PS), the Compulsive Internet Use Scale (CIUS), the Rosenberg Self-Esteem Scale (RSE), and the Interpersonal Emotion Regulation Questionnaire (IERQ) for data collection. Results The results showed evidence of phubbing among approximately half of the students. Statistically significant differences were found based on gender and educational level in the Phone Obsession subscale and the PS total score, with male students and university students scoring higher in their respective parameters. In addition, phubbing was positively correlated with problematic internet use and negatively correlated with self-esteem. Conclusion Phubbing behavior is highly prevalent among adolescents aged 12–21 years and is positively correlated with low self-esteem and problematic internet use. Developing strategies for addressing this widespread issue at early ages, particularly within the educational context, such as schools, is crucial for implementing preventive measures. The inappropriate use of technological devices, including smartphones, in schools has the potential to negatively affect students’ well-being and ability to adapt to school.